IMPACT OF SILVER CRAFT DEVELOPMENT ON SOCIO-ECONOMIC CONDITIONS IN KOTAGEDE DISTRICT - Hati Sri Pratami; Joni Purwohandoyo; Untari Eka Setiawati (Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to identify the dynamics of the development of the silver craft industry in Kotagede District, identify aspects related to the problems of the silver craft business, and analyze the influence of the development of the silver craft industry on the socio-economic conditions of household business actors. The study uses a descriptive approach with qualitative and quantitative methods. Data were collected through structured interviews, field observations, and documentation. The analysis technique used is descriptive with the presentation of data in the form of tables and diagrams. The results show that the silver industry is a small and medium industry, and the development of the silver craft industry has a significant impact on the income of business actors, ownership of household assets, and children's education.